2015
DOI: 10.1097/cin.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Theoretical Frameworks and the Conceptual Factors in the Adoption of Clinical Decision Support Systems

Abstract: The clinical decision support system is utilized to translate knowledge into evidence-based practice in clinical settings. Many studies have been conducted to understand users' adoption of the clinical decision support system. A critical review was conducted to understand the theoretical or conceptual frameworks used to inform the studies on the adoption of the clinical decision support system. The review identified 15 theoretical and conceptual frameworks using multiple hybrids of theories and concepts. The T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…A systematic review of research on the public acceptance of GMF and nuclear energy was conducted following the PRISMA guidelines which include the identification of: information sources, search criteria, and study selection criteria (Liberati et al 2009). PRISMA protocols are well supported in the literature and employed in several similar studies (Cameron et al 2014;Khong et al 2015;Pidgeon et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of research on the public acceptance of GMF and nuclear energy was conducted following the PRISMA guidelines which include the identification of: information sources, search criteria, and study selection criteria (Liberati et al 2009). PRISMA protocols are well supported in the literature and employed in several similar studies (Cameron et al 2014;Khong et al 2015;Pidgeon et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…We will include constructs that we consider relevant to understand the determinants of behavioral change and technology acceptance, but are not included in all contributing frameworks. Example: a recent literature review from Khong et al [ 29 ] identified “threats to professional autonomy” as a determinant of the acceptance of DDSs. It could be argued that this construct could be considered part of the UTAUT’s “performance expectancy.” However, it could be useful to include this construct in the final framework specifically.…”
Section: Methodsmentioning
confidence: 99%
“…We will map constructs that we consider too specific to more abstract constructs included in other frameworks. Example: the same review from Khong et al [ 29 ] includes “usability” and “computer experience or computer skill” as determinants for DSS acceptability. These two constructs could be mapped to the UTAUT’s “effort expectancy.” Therefore, it could be argued that it would not be necessary to include them in the final framework.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, several models attempt to explain the factors influencing the user’s decision to use a technology system routinely [ 33 , 34 ]. Furthermore, several recent studies have identified determinants that are specific to the acceptance of CDSSs [ 35 - 40 ]. When seen together, these frameworks amount to too many concepts for a reasonable research project to use effectively.…”
Section: Introductionmentioning
confidence: 99%